Volume‐rendered optical coherence tomography angiography during ocular interventions: Advocating for noninvasive intraoperative retinal perfusion monitoring. Issue 12 (11th September 2022) - Enz, Tim J.; Maloca, Peter M.; Tschopp, Markus; Menke, Marcel N.; Tribble, James R.; Williams, Pete A.; Inglin, Nadja; Steitz, Ulrike; Scholl, Hendrik P. N.; Papazoglou, Anthia
Abstract: We aimed to test for feasibility of volume‐rendered optical coherence tomography angiography (OCTA) as a novel method for assessing/quantifying retinal vasculature during ocular procedures and to explore the potential for intraoperative use. Thirty patients undergoing periocular anaesthesia were enrolled, since published evidence suggests a reduction in ocular blood flow. Retinal perfusion was monitored based on planar OCTA image‐derived data provided by a standard quantification algorithm and postprocessed/volume‐rendered OCTA data using a custom software script. Overall, imaging procedures were successful, yet imaging artifacts occurred frequently. In interventional eyes, perfusion parameters decreased during anaesthesia. Planar image‐derived and volume rendering‐derived parameters were correlated. No correlation was found between perfusion parameters and a motion artifact score developed for this study, yet all perfusion parameters correlated with signal strength as displayed by the device. Concluding, volume‐rendered OCTA allows for noninvasive three‐dimensional retinal vasculature assessment/quantification in challenging surgical settings and appears generally feasible for intraoperative use. Abstract : In ophthalmic surgery, intraoperative retinal perfusion assessment/monitoring has been suggested for numerous indications, typically using fluorescence angiography. However, applicability is limited given the difficult arrangement, associated risks and the lack of automated/objective perfusion quantification. This study demonstrates that volume‐rendered OCTA allows for noninvasive three‐dimensional retinal vasculature assessment/quantification at the micron‐level in a challenging surgical setting. These findings warrant further research to explore the potential of this technology for intraoperative use. With credits to Prof. Rick Spaide and Dr. Peter Maloca.